The Key Concepts and Elements of Installation Art - Tengku Azhari Tengku Azizan, (Wacana Seni Journal of Arts Discourse, 2007)
Installation art has been predominantly perceived as another genre in contemporary art ramification, as earller attempts by theorists and historians in defining installation art, has put the question into polemical argumentation rather than academic investigation. Early incomprehensive investigation failed to decipher the definitive characteristic of this emerging visual art practice when installation art was defined by its medium alone (De Olivera 2003). The conventional approach to define installation art which is bound by traditional formulism has restricted the genre from being flexible and fluid. This has led some artists to misinterpret installation art as an art of display or installation of objects. Taking media as the most important element in characterizing installalion art is also contradictory to the nature of the practice itself,  which is to challenge its boundaries. Media does not have the capacity to be the only element in defining installation art.